Effects of a successful mathematics classroom framework on students' mathematics self-efficacy, motivation, and achievement: a case study with freshmen students at a university foundation programme in Kuwait. Issue 6 (2nd May 2022) - Hammad, Sali; Graham, Ted; Dimitriadis, Christos; Taylor, Annette
Abstract : Designed for this study as a conceptual framework comprising particular educational approaches and techniques for mathematics teaching and learning, the Successful Mathematics Classroom (SMC) aimed to promote college students' mathematics self-efficacy, motivation, and achievement. Through using a case study methodology, a range of tests and interviews, we investigated the effects of the SMC on a sample of 130 freshmen students from a mathematics foundation programme in everyday classroom practice. The results showed a positive correlation between students' self-efficacy and achievement, as well as their motivation and achievement. The results further revealed that there was a positive impact of using the SMC framework on students' mathematics self-efficacy, motivation, and performance. The elements with most impact were teacher's teaching methodology, group work, teacher's attitude, and gamification. Further research is recommended to examine the effects of SMC in different education settings, different students, teaching styles, and larger sample sizes.